Strategi Nafkah Petani Perkotaan Pulau Kecil (Studi Kasus Kecamatan Leitimur Selatan Kota Ambon) - August Ernst Pattiselanno; Edizon Jambormias; Junianita Fridianova Sopamena (Institut Teknologi Sepuluh Nopember, 2018)
The objective of this research was to analyze livelihood strategies designed by the societies in small islands. Research was located in South Leitumur District, Ambon City. Site of research was two sub-districts, namely Hutumuri and Leahari. Sample of farmers were determined purposively from both sub-districts, resulting in 69 farmers, precisely 51 farmers in Hutumuri and 18 farmers in Leahari. Data were collected from depth interview, and analyzed with simple tabulation accompanied with descriptive explanation. Result of research indicated that there are three livelihood strategies designed by coastal societies in South Leitimur District, respectively: developing natural/farming resource potentials by increasing the quantity of commodities that have potential capability to satisfy daily necessities; developing natural/farming resource potentials in wider sense, which concerns with developing potentials of coastal area as fishing spot; and developing human resource potentials by providing job opportunity out of farming and improving the existing skills owned by farmer household.